2015
DOI: 10.1080/00380768.2015.1052985
|View full text |Cite
|
Sign up to set email alerts
|

pH effects of the addition of three biochars to acidic Indonesian mineral soils

Abstract: Soil acidity may severely reduce crop production. Biochar (BC) may increase soil pH and cation exchange capacity (CEC) but reported effects differ substantially. In a systematic approach, using a standardized protocol on a uniquely large number set of 31 acidic soils, we quantified the effect of increasing amounts (0-30%; weight: weight) of three types of field-produced BCs (from cacao (Theobroma cacao. L.) shell, oil palm (Elaeis guineensis. Jacq.) shell and rice (Oryza sativa. L.) husk) on soil pH and CEC. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 50 publications
8
41
1
9
Order By: Relevance
“…This was the reason for setting 0.2 mS cm -1 as EC threshold in the pretreatment. Previous research (Martinsen et al, 2015) using a sub sample of the same cacao shell biochar showed that CEC-BC without any pretreatment was 197 cmol(+)/Kg, while in our experiment this was 59.1 cmol(+) Kg -1 with pretreatment. Furthermore, Graber et al (2017) found significant differences between CEC-BC and CEC-NH4 + for some of the biochars they analyzed.…”
Section: Cations Removed In the Pretreatment Vs Exchangeable Cationscontrasting
confidence: 57%
See 1 more Smart Citation
“…This was the reason for setting 0.2 mS cm -1 as EC threshold in the pretreatment. Previous research (Martinsen et al, 2015) using a sub sample of the same cacao shell biochar showed that CEC-BC without any pretreatment was 197 cmol(+)/Kg, while in our experiment this was 59.1 cmol(+) Kg -1 with pretreatment. Furthermore, Graber et al (2017) found significant differences between CEC-BC and CEC-NH4 + for some of the biochars they analyzed.…”
Section: Cations Removed In the Pretreatment Vs Exchangeable Cationscontrasting
confidence: 57%
“…Biochar is a carbon-rich product made by pyrolysis of organic waste, which may be used as a soil enhancer. Particularly, in tropical soils biochar has been shown to have a positive impact on soil fertility, including increased potassium (K + ) content, pH, water retention capacity, and cation exchange capacity (Jeffery et al, 2011;Liang et al, 2006;Martinsen et al, 2015), which all contribute to increased crop yield (Jeffery et al, 2017). Moreover, biochar is emerging as an alternative for heavy metal remediation in soil and water (Ahmad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The biochars produced at lower‐temperature may probably possess more organic functional groups of COOH and C‐OH and subsequently increasing nutrient retention sites compared to high‐temperature biochars (Ippolito et al, ). The increase in the pH of biochar‐amended soils could be due to (a) the alkalinity of biochar produced from high‐temperature pyrolysis (Martisen, Alling, Nurida, et al, ); (b) the formation of negatively charged carboxyl, hydroxyl, and phenolic functional groups on the surface of biochar material, which reduces the H + concentration in soil solutions (Wang et al, ); and (c) the presence of carbonates, silicates, ash contents, and bicarbonates that bind H + from soil solution (Martisen et al, ; Wang et al, ). Generally, the amelioration effects of biochar addition to soils are mainly dependent on both the feedstock type and the processing temperature (Abbasi & Anwar, ; Usman et al, ).…”
Section: Biochar As Soil Amelioratormentioning
confidence: 99%
“…While until now positive yield responses to biochar applications have almost exclusively been obtained on poor and degraded soils (Biederman & Harpole, 2013;Cornelissen et al, 2013), all soils of the present biochar field trials can be considered as relatively fertile with their SOM contents ranging from 2·3 to 9·2% and soil pH values ranging from 4·5 to 6·1 with two exceptions at 4·1 and 3·8. Several authors showed that biochar may have a liming effect which depends on biochar and soil type (Silber et al, 2010;Butnan et al, 2015;Camps-Arbestain et al, 2015;Jeffery et al, 2015;Martinsen et al, 2015). Moreover, Jeffery et al (2015) showed in his meta-analysis a clear dependency of biochar-caused yield increases on the initial soil pH.…”
Section: Basic Biochar-related Mechanismsmentioning
confidence: 99%